Chad Growth and Diversification : Leveraging Export Diversification to Foster Growth - World Bank (World Bank, Washington, DC, 2019)
This report describes the key policies for Chad to successfully leverage export diversification to foster economic growth. After several unsuccessful attempts at diversifying in the 1990s, Chad has deepened its dependence on commodities, mainly relying on oil; which came to replace cotton. However, the experience of other countries, in Africa and other parts of the world, shows that while large scale production of oil resources offers great opportunities, it comes with major shortcomings. Chad’s Vision 2030 is to become an emerging economy, driven by diversified and sustainable sources of growth. The goal is to triple the average GDP per capita at current prices, by increasing it from US$ 730 in 2014 to US$ 2300 in 2030, while drastically reducing the poverty rate from 46.7 percent in 2011 to 8 percent during the same period. Chad’s economy is overly dependent on crude petroleum, which makes it vulnerable to external shocks. Therefore, to achieve this development goal, only an export diversification strategy can foster a larger menu of goods and services than can become growth-accelerating and job-creating activities. Its implementation challenges are formidable, but the country has little choice, as the social unrest following recurrent oil price slumps, its burgeoning youth population and regional security threats may foment more violence in an already fragile and volatile economy and keep investors away. Hence, this report outlines a strategy to achieve this vision centered on the diversification of its non-oil economy (mainly agricultural-based exports) away from natural resource-based commodities.